2016
DOI: 10.1177/0013916516629191
|View full text |Cite
|
Sign up to set email alerts
|

Raising Students Awareness to Climate Change

Abstract: Much energy and money is dedicated to increasing climate change awareness and pro-environmental behaviors. Mere communication campaigns, which are often alarmist, are widely used despite their uncertain effectiveness. We suggest that using binding communication strategies would prove more adequate. Binding communication consists in combining a persuasive message and a preparatory act linked to the persuasive message. This procedure is generally reported to be more efficient than a single persuasive message at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Although CC knowledge and trust in institutions showed significant correlations with PEBs, attitudes and self-efficacy exhibit a much stronger relationship, which is why it could be fruitful to focus strategies on these dimensions. Following Spence and Pidgeon (2010), emphasizing on the potential negative impacts of not carrying out actions, abandoning alarmist paradigms, and generating more binding strategies (combining personal and collective solutions) -arise as directive vectors, which have been proven useful techniques for students (Parant et al, 2016). Nevertheless, transmission of motivational communication should be carried out carefully, as people may not respond adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Although CC knowledge and trust in institutions showed significant correlations with PEBs, attitudes and self-efficacy exhibit a much stronger relationship, which is why it could be fruitful to focus strategies on these dimensions. Following Spence and Pidgeon (2010), emphasizing on the potential negative impacts of not carrying out actions, abandoning alarmist paradigms, and generating more binding strategies (combining personal and collective solutions) -arise as directive vectors, which have been proven useful techniques for students (Parant et al, 2016). Nevertheless, transmission of motivational communication should be carried out carefully, as people may not respond adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing about climate change is not enough; it is necessary to make people feel its impact in order to increase their attention, interest and willingness to take action. There is no magic formula to find the right emotive aspects of a game; however, research in the field of climate change communication has revealed that if imagery and messages in the game increase worry or fear, these should be accompanied by feelings associated with remedial action and solutions, linking to individuals' everyday emotions in the context of climate change; otherwise, it can make them feel helpless and overwhelmed (ONeill and Nicholson-Cole 2009;Parant et al 2017).…”
Section: Meaningful: Evoking Intense Feelingsmentioning
confidence: 99%
“…They examined climate change awareness among undergraduate students. Pandve and Raut [22], examined climate change knowledge among medical students, Rahman et al [23] studied climate change awareness among high school students, Parant et al [24] inquired into how to raise students' awareness on climate change, and Frejie [25] assessed global warming awareness among university of Bahrain science students. Ayanlade and Jegede [26] studied climate change education and knowledge among university graduates in Nigeria whilst Buggy and McGlynn [27] studied climate change awareness among Tanzania's second-level education system.…”
Section: Introductionmentioning
confidence: 99%